THE INFLUENCE OF SOCIAL MEDIA ON ENGLISH LANGUAGE USE AMONG YOUTH (International journal of artificial intelligence, 2025)
This article examines the influence of social media on young people’s English language use, highlighting both its positive and negative impacts. The study draws upon the theories of David Crystal (2011) and Dashiel (1952), who both emphasized the adaptive nature of language. Supporting their views, this paper argues that social media acts as a modern environment for linguistic evolution, where English constantly changes through informal digital communication. However, while this development fosters creativity and global communication, it can also contribute to a decline in formal writing standards. Furthermore, through examples and analysis, this research provides evidence that social media platforms not only serve as learning tools but also reshape linguistic identity among youth.